Development and validation of a short nutrition literacy scale for young adults - Vrinten, Jules; Van Royen, Kathleen; Pabian, Sara; De Backer, Charlotte; Matthys, Christophe (Frontiers in Nutrition, 2023)
Background: Due to their high media use, young adults are frequently exposed to contradictory or even erroneous nutrition information. To properly handle and critically assess nutrition information, young adults (both general population and patient populations) need adequate levels of nutrition literacy. Currently there is a lack of suitable instruments to measure nutrition literacy in young adults (18-25 years). Therefore the aim of this study was to develop and validate a Short Nutrition Literacy (S-NutLit) scale for use in this age group. Methods: Development and validation of the S-NutLit consisted of six phases: (1) item generation based on literature, (2) expert assessments to evaluate content validity, (3) cognitive interviews with the target population to assess face validity and readability, (4) pre-test to reduce the number of items, (5) validation survey to assess dimensionality with exploratory factor analyses, internal reliability with Cronbach alpha, construct and criterion validity by examining associations with age, gender, education level, health literacy, general literacy, dietary behaviors and physical activity with correlations, ANOVAs, and t-tests, (6) two-week follow-up survey to assess test-retest reliability with intra-class correlations. Results: Starting from an initial pool of 53 items, expert assessments and cognitive interviews led to the reformulation, removal, and construction of items. Young adults aged 18-25 years participated in cognitive interviews (n = 12), pre-test (n = 101), validation survey (n = 300), and reliability survey (n = 92). The final S-NutLit consisted of 11 items rated on a 5-point scale distributed across two subscales (i.e. information skills and expert skills). Cronbach alpha values ranged from 0.79 - 0.83 and intraclass correlations from 0.61 - 0.79 (p < .001). Significant associations were observed with health literacy (r = 0.27, p < .001), general literacy and numeracy (rs = 0.12, p = .046), and education level (rs = 0.13, p = .025). Conclusions: Findings indicate that the S-NutLit is a valid and reliable tool to assess nutrition literacy among young adults. The S-NutLit fills a gap in the field by offering a short measure of nutrition literacy and may be incorporated in digital technology to support the nutrition care process.